Current Situation of Availability and CostEffectiveness Analysis of Selected Drugs inAnantapur, AP, India - Meenu Singh,Y. Pragzna, Dharma Dev Bommi (Journal of Applied Pharmaceutical Science)
World Health Organization (WHO) and Health Action International (HAI) recognized the need for a standard methodology to measure medicine prices in countries so that a clearer picture of what patients actually pay for medicines in low and middle-income countries could be obtained. These two organizations jointly published a manual, which described a methodology for collecting data and measuring medicine prices in various countries. By adopting this methodology, in present study we focused to obtain 1. Baseline data for the availability of medicines in the public and private sectors, 2. Cost Effectiveness Analysis or Affordability of model treatment regimen and 3. Comparison of national Most Sold Generics/MSGs in Anantapur. We did our survey in four phases namely survey planning and preparation, sampling, selection of medicines, MSG equivalents, affordability/ cost effectiveness analysis and availability. The results of the study provided stable baseline interventions to improve the availability of medicines in the public sector and reduce the prices in private sector.
Keywords: Affordability/ Cost effectiveness Analysis,Availability,MSGs (Most sold Generics),WHO (World Health Organization),HAI (Health Action International).